TOTAL QUALITY MANAGEMENT (TQM) DALAM KONTEKS PENDIDIKAN - Maryamah Maryamah (Ta'dib: Jurnal Pendidikan Islam, 2013)
Management of educational quality improvement is the integration of all function and processes within an educational organization in order to achieve continuous improvement of the quality of school outputs and services. The main objective is the satisfactions of the clients or customers. In the educational or school organization, there are three basic definitions of quality assurance, contract conformance, and customer driven. The application of TQM in the context of educational organizations is based on a framework that educational managers are able to make the process of improvement.